INVESTIGATION OF GROUND AND FOUNDATION CONDITION INFLUENCE ON THE SPASO-PREOBROZHENSKAYA CHURCH CONSTRUCTIONS IN POLOTSK (Academic journal Industrial Machine Building Civil Engineering, 2017)
In the article the problems of the XII century architecture monument preservation – Spaso-Preobrazhenskaya church of Spaso-Efrosinievskiy convent in Polotsk are considered. A brief reference is given on the technical condition and design features of the facility. Various parameters research results allows to estimating  bearing constructions technical condition. The issues of bearing structure geodetic, visual, instrumental and electronic remote monitoring complex implementation and organization are considered. The issues of innovative technology introduction for this research area such as ground-based three-dimensional laser scanning are covered. There was made a conclusion church foundation conditions and there are given recommendations as for their strengthening.
Keywords: foundation; church; architectural monument; laser scanning; monitoring of building structures